Risk Factors and Biomarkers for Pulmonary Toxicities Associated with Immune Checkpoint Inhibitors - Efraim Guzel; Ismail Hanta; Oya Baydar Toprak; Okan Gurbuz; Burak Mete; Ertugrul Bayram (Medicina)
Background and Objectives: Immune checkpoint inhibitors (ICIs) have emerged as groundbreaking agents in cancer therapy; however, their immune-related adverse effects, especially pulmonary toxicity, significantly limit their use. This study aimed to determine the incidence and risk factors associated with ICI-induced pulmonary toxicity. Materials and Methods: We conducted a prospective observational study involving 126 patients aged ≥18 years with malignancies treated with ICIs between April 2022 and April 2024. Patients were followed every six months over a two-year period. Clinical, laboratory, and radiological data were collected to assess pulmonary toxicity. Results: The mean age of our patients was 62.93 ± 12.94 years, and 81% were male. The ICI-related pulmonary toxicity rate was 16.7%, and the all-cause mortality rate was 68.3%. In the analysis, the conditions associated with pulmonary toxicity were the type of malignancy, the presence of lung cancer, COPD, long-term ICI use, dyspnea, cough and sputum, the pre-ICI lung nodule mass, and high blood monocyte levels. Our regression analysis results for the determination of risk factors showed a 7.70-fold increase in the presence of cough symptoms, a 4.57-fold increase in the presence of COPD, a 0.998-fold increase for every 1 unit decrease in lymphocyte count, and an 11.75-fold increase in risk for a monocyte count of 130 or less. Conclusions: Our study’s findings suggest that patients with identifiable risk factors for pulmonary toxicity should undergo closer monitoring and early diagnostic evaluation during ICI therapy to reduce morbidity and mortality.